Leaf arginine spraying improves leaf gas exchange under water deficit and root antioxidant responses during the recovery period - Silveira, Neidiquele M (Plant physiology and biochemistry : PPB, 2021)
Copyright © 2021 Elsevier Masson SAS. All rights reserved.